2000
DOI: 10.1046/j.1537-2995.2000.40101214.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an automated system for the collection of packed RBCs, platelets, and plasma

Abstract: Blood components collected with the Trima are equivalent to currently available components, and they meet the applicable regulatory standards. This system provides consistent, standardized components with predictable yields. It provides the option of fully automating the collection of all blood components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 29 publications
(30 reference statements)
4
35
0
Order By: Relevance
“…The 24-hour RBC recovery determined by FC was 78.0 ± 12.0% (mean ± SD), 78.0 ± 15.0% when labeled RBCs originated from donor and 78.6 ± 11.6% when labeled RBCs originated from the recipient. These data are comparable to those published by Elfath et al [26] who measured a 24-hour RBC recovery of 76.8 ± 3.1% for RBC units collected with automated apheresis and a recovery of 77.1 ± 4.4% for whole-blood RBCs using 51 CR. However, it is not clear if the FDA criteria of more than 75% recovery for RBC units would have been met in our study if all RBCC were transfused at the end of the storage period.…”
Section: ----------------------------------------------------------supporting
confidence: 90%
“…The 24-hour RBC recovery determined by FC was 78.0 ± 12.0% (mean ± SD), 78.0 ± 15.0% when labeled RBCs originated from donor and 78.6 ± 11.6% when labeled RBCs originated from the recipient. These data are comparable to those published by Elfath et al [26] who measured a 24-hour RBC recovery of 76.8 ± 3.1% for RBC units collected with automated apheresis and a recovery of 77.1 ± 4.4% for whole-blood RBCs using 51 CR. However, it is not clear if the FDA criteria of more than 75% recovery for RBC units would have been met in our study if all RBCC were transfused at the end of the storage period.…”
Section: ----------------------------------------------------------supporting
confidence: 90%
“…The functional range of pH has long been recognized as an important factor for storage. Figure 3 summarizes platelet recoveries versus pH for several of the historical studies plus more recent studies conducted with platelets stored in ELP bags 6,21,22 . Low pH was observed in 1 of 24 components in this study.…”
Section: Discussionmentioning
confidence: 81%
“…It has been previously demonstrated that different cell separators induce different degrees of PLT activation, depending on their collection modalities 7‐9 , 21,23‐25 . Plateletpheresis, obtained using the surge technology, like those obtained with the Haemonetics MCS device, show lower levels of P‐selectin when compared to those obtained using Cobe Spectra or CS‐3000 machines 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Multicomponent collection, which is the contemporary yield of RBCs and plasma, or plasma and PLTs, or RBCs and PLTs, has been recently introduced into blood collection center practices. This new donor apheresis technique, mostly performed through single‐vein access, allows the production of a leukoreduced plateletpheresis containing more than 3 × 10 11 PLTs in a consistent proportion of units (>75%) and the contemporary collection of a subsidiary 200‐ to 400‐mL plasma unit in 45 to 60 minutes 7‐9 …”
mentioning
confidence: 99%